To remove or not to remove: Intraconal metallic foreign body: case report - Subedi, Kumudini; Pradhan, Sangita; Byanju, Raghunandan (Journal of Karnali Academy of Health Sciences, 2024)
Background: Foreign bodies (FB) are implicated in 17-30% of penetrating ocular injuries. We encountered 2 cases of perforating ocular trauma with metallic intra-orbital FB in 2 teenage males. Case report: A 17-year-old male presented with a nail-hammer injury 6 hours after trauma. Snellen’s acuity was 3/60 with a corneal laceration of 5mm with lens matter in the anterior chamber and vitreous hemorrhage. After primary repair by the anterior segment surgeon, posterior segment surgery was done following the diagnosis of retinal detachment (RD) and intra-ocular Foreign Body(FB) by ultrasound. No FB was noted intraoperatively. On Computerized Tomography (CT), metallic FB 5.2x3.5 mm was noted at the insertion of the inferior oblique muscle. Removal of IOFB was deferred by the oculoplasty department. Delayed oil removal was done with final Snellen’s acuity 6/12p. Another 16-year-old male attended the retina clinic 20 days after injury with a metalon-metal hammering incident. Primary topical management was done elsewhere. Snellen’s acuity was 6/18p in the affected eye. The site of FB entry was scleral,1.4 mm from limbus at 9 o’clock with no associated lens trauma. CT scan of the brain and orbit showed intra-orbital FB medial to the medial rectus near the orbital apex. FB (4.4x4.3 mm) left a tract in subretinal space to enter intraconal space 1 disc diameter nasal to optic disc. Vitrectomy was done for tractional RD and postoperative Snellen’s vision was 6/12. Conclusion: A high degree of clinical suspicion is necessary to detect and localize IOFB. Non-toxic intra-orbital FB may be left in the context of good vision in the affected eye and possible iatrogenic optic nerve damage.